1990
DOI: 10.1126/science.2105529
|View full text |Cite
|
Sign up to set email alerts
|

Grafts of Fetal Dopamine Neurons Survive and Improve Motor Function in Parkinson's Disease

Abstract: Neural transplantation can restore striatal dopaminergic neurotransmission in animal models of Parkinson's disease. It has now been shown that mesencephalic dopamine neurons, obtained from human fetuses of 8 to 9 weeks gestational age, can survive in the human brain and produce marked and sustained symptomatic relief in a patient severely affected with idiopathic Parkinson's disease. The grafts, which were implanted unilaterally into the putamen by stereotactic surgery, restored dopamine synthesis and storage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
427
0
6

Year Published

1990
1990
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 1,104 publications
(439 citation statements)
references
References 22 publications
6
427
0
6
Order By: Relevance
“…Previous studies have shown that cell replacement therapy using fetal tissue may be a viable treatment option for PD [4][5][6][7][8] and HD. [9][10][11][12] In the case of PD, two double-blind studies sponsored by National Institutes of Health (NIH) found that the transplantation of fetal DA neurons into the brain of PD patients resulted in modest functional benefits but also caused undesirable side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that cell replacement therapy using fetal tissue may be a viable treatment option for PD [4][5][6][7][8] and HD. [9][10][11][12] In the case of PD, two double-blind studies sponsored by National Institutes of Health (NIH) found that the transplantation of fetal DA neurons into the brain of PD patients resulted in modest functional benefits but also caused undesirable side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Dopaminergic Grafts Can Survive and Become Morphologically Integrated in the PD Patient's Brain Following implantation of postmitotic DA neuroblasts from the ventral mesencephalon of 6-to 9-weekold human fetuses, positron emission tomography (PET) detected increases in 6-L-[ 18 F]-fluorodopa ( 18 F-dopa) uptake ( Fig. 1) [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], and histopathological studies have shown long-term, extensive synaptic reinnervation in the striatum [13,[20][21][22][23][24][25][26][27].…”
Section: Can Da Neurons Be Replaced and Neural Grafts Have Functionalmentioning
confidence: 99%
“…Unilateral transplantation of fetal tissue was used in the first human clinical Parkinson's disease transplant trials [3,4,38]. Typically implants were made into the side of brain contralateral to the side of the body with the worse Parkinson's symptoms.…”
Section: Unilateral Versus Bilateral Transplantationmentioning
confidence: 99%
“…Therefore, we did not use immunosuppression in our double-blind transplant study [7]. The Lund group chose to use immunosuppressants at doses equivalent to those given to kidney transplant patients [4]. When Freeman et al [43] and Olanow et al [9] started their transplant program approximately 5 years after our group and the Lund group, they took a middle ground, using short-term immunosuppression of 6 to 18 months.…”
Section: Immunology Of Transplantsmentioning
confidence: 99%
See 1 more Smart Citation